Exploring the origins of burnout among secondary educators - Van Tonder, Christian Louis; Williams, C. (OpenJournals Publishing, 2009)
Orientation: Maslach and Leiter (1997) have suggested that burnout constitutes an erosion of the soul. Burnout is a non-discriminatory phenomenon with a pronounced negative impact on the individual employee and the organisation and is particularly prevalent among educators. Research purpose: This study aimed to explore the probable reasons for burnout among secondary educators. Study motivation: Several South African studies have focused on the phenomenon of burnout among educators but the probable reasons for burnout in this population have not yet received adequate attention. This study extended earlier international research that probed this facet. Research design, approach and method: A mixed-methods design with a predominantly qualitative methodology was employed to explore the probable reasons for burnout among 59 educators from three urban secondary schools in Gauteng, South Africa. Data comprised Maslach Burnout Inventory-General Survey protocols and rich data work descriptions. Semi-structured interviews were also conducted with the five participants who tested highest on the burnout indicators. Main findings: The results indicated that a negative learner profile and workload were the most frequently cited reasons for potential burnout. Practical/managerial implications: Burnout requires considered attention and aggressive context specific intervention to contain its negative impact on both the educator and the student learning experience.